Socio-religious Sampradaya Jnana Buddha Siwa in Lombok Community - I Wayan Wirata (Politeknik Negeri Bali, 2020)
The Jnana Buddha Siva ritual is an implementation part of Siva Siddhanta. The implementation of the teaching implies the existence of the spirit (Atman) who resides in each individual. This is done as part of the devotee's experience and knowledge (Bhakta) in carrying out his spiritual activities. In implementing the teachings of Jnana Buddha Siva is always oriented to the greatness of Siva as the focus of worship offerings of the Almighty God. The observation was carried out on the informant of Sampradaya Jnana Buddha Siva as such: follower and head or other informants who knew Jnana Buddha Siwa Teaching. The analysis was carried out with data and information from Sampradaya Jnana Buddha Siva. The results showed as follows: The form of socio-religious of Sampradaya Jnana Buddha Siva in Lombok, West Nusa Tenggara through sympathetic communication; Barriers to socio-religious that are faced with it is not the implementation of religious activities carried out jointly, because there are differences in the procedures for carrying out religious activities between Sampradaya Jnana Buddha Siva with Lombok West Nusa Tenggara people; and the impact of socio-religious carried out is the increasingly close relationship between the Jnana Buddha Siva with the people of Lombok, where the Jnana Buddha Siva feel themselves to be part of the citizens of the West Nusa Tenggara community in general and Lombok in particular. The implication of this study, such as increasing integration of Hindu community, development of Hindu religion, and enhancing cohesiveness members of Buddha Siva teaching.